IDENTIFIKASI CEMARAN LOGAM BERAT (Hg, Cu, Pb, Zn, As, dan Ag) PADA KERANG HIJAU (Perna viridis) DI PULAU PASARAN PROVINSI LAMPUNG Identification of Heavy Metals Contens (Hg, Cu, Pb, Zn, As, And Ag) in Green Mussels (Perna Viridis) at Pasaran Island Lampung Province - Fauzan, Muhammad Ridho; Rangga, Azhari; Astuti, Sussi; Suroso, Erdi (Jurusan Teknologi Hasil Pertanian, 2024)
This study aims to determine the content of heavy metals Hg, Cu, Pb, Zn, As, and Ag in green mussels (Perna viridis) at Pasaran Island. Sampling of green mussels was carried out on Pasaran Island and Qiluith Green Shells Cages in two replications. The results showed that the green clams from Pasaran Island were contaminated with Hg of 0.05 mg/kg, Cu of 2.84 mg/kg, Pb of <0.4 mg/kg, Zn of 9.04 mg/kg, As of 0.045 mg/kg, and Ag of <0.1 mg/kg, while those from the Green Qiluith contaminated with Hg of 0.055 mg/kg, Cu of 3.82 mg/kg, Pb of <0.4 mg/kg, Zn of 11.7 mg/kg, As of 0.035 mg/kg, and Ag of <0.1 mg/kg. Heavy metals content in the green mussels sample on Pasaran Island and Qiluith Green Shells Cages for Mercury (Hg) metal was 0,05 mg/kg and 0,055 mg/kg, Lead (Pb) was <0,4 mg/kg, and Arsenic (As) of 0,045 mg/kg and 0,035 mg/kg still meet the limit of heavy metals contamination in shellfish according to SNI 7387 of 2009. The limits of heavy metals contamination of Copper (Cu), Zink (Zn), and Silver (Ag) have not determined in SNI 7387 of 2009, however, the heavy metal content of Cu and Zn are classified as high compared to Hg, Pb, and As.